2017
DOI: 10.1371/journal.pone.0188256
|View full text |Cite
|
Sign up to set email alerts
|

Age of heart disease presentation and dysmorphic nuclei in patients with LMNA mutations

Abstract: Nuclear shape defects are a distinguishing characteristic in laminopathies, cancers, and other pathologies. Correlating these defects to the symptoms, mechanisms, and progression of disease requires unbiased, quantitative, and high-throughput means of quantifying nuclear morphology. To accomplish this, we developed a method of automatically segmenting fluorescently stained nuclei in 2D microscopy images and then classifying them as normal or dysmorphic based on three geometric features of the nucleus using a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…We also found that there were no significant changes in LMNA transcript levels, ratio of Lamin A to Lamin C transcripts, or expression of other NL-genes, LMNB1 and LMNB2 between the Patient group and two control groups. These results are in line with our previous structural studies that found no significant difference in nuclear abnormalities and suggests that there were no compensatory mechanisms at the transcription level for the other proteins that construct the nuclear lamina [63].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found that there were no significant changes in LMNA transcript levels, ratio of Lamin A to Lamin C transcripts, or expression of other NL-genes, LMNB1 and LMNB2 between the Patient group and two control groups. These results are in line with our previous structural studies that found no significant difference in nuclear abnormalities and suggests that there were no compensatory mechanisms at the transcription level for the other proteins that construct the nuclear lamina [63].…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, there is aberrant upregulation of ERK/MAPK pathway in affected tissues such as LMNA mutant cardiomyocytes which leads to laminopathy phenotype [ 10 , 62 ]. Together, these mechanisms may provide an explanation for the absence of any significant phenotype in fibroblasts [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of a conclusion would have been impossible with bulk RNA sequencing. In the future, this approach can also be utilized to look at other families with similar mutations 15 , 72 as well as sex as a biological variable. This would require significantly more individuals to be analyzed with the assays detailed here, which was beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…Substrates were fabricated for structural studies as described previously [5,8,19,24,46]. Briefly, large cover glass (Brain Research Laboratories, Newton, MA) was cleaned by sonicating, then spin coated with 10:1 Polydimethylsiloxane (PDMS; Ellsworth Adhesives, Germantown, WI).…”
Section: Substrate Preparation and Extracellular Matrix Patterningmentioning
confidence: 99%